Angiopoietin-2 Is an Early Indicator of Acute Pancreatic-Renal Syndrome in Patients with Acute Pancreatitis - Mateusz Sporek; Paulina Dumnicka; Agnieszka Gala-Bladzinska; Piotr Ceranowicz; Zygmunt Warzecha; Artur Dembinski; Ewa Stepien; Jerzy Walocha; Ryszard Drozdz; Marek Kuzniewski; Beata Kusnierz-Cabala (Hindawi Limited, 2016)
Within the first week of the disease, acute kidney injury (AKI) is among the most common causes of mortality in acute pancreatitis (AP). Recently, serum angiopoietin-2 (Ang-2) has been associated with hyperdynamic state of the systemic circulation. The aim of this study was to examine the associations between Ang-2 and the clinical AP severity during the first 72 hours of the disease, and organ disfunction, including AKI. Methods. Study included patients admitted to the surgery ward, diagnosed with AP. AKI was diagnosed according to KDIGO guidelines and renal failure according to modified Marshall scoring system. Ang-2 was determined in serum with ELISA. Results. AP was classified as mild (MAP) in 71% of patients, moderately severe (MSAP) in 22%, and severe (SAP) in 8%. During the first 72 hours of AP, 11 patients developed AKI and 6 developed renal failure. Ang-2 at 24, 48, and 72 hours following the onset of AP symptoms significantly predicted SAP and MSAP, as well as AKI and renal failure. Also, Ang-2 significantly correlated with acute phase proteins as well as with the indicators of renal disfunction. Conclusions. Serum Ang-2 may be a relevant predictor of AP severity, in particular of the development of AP-renal syndrome.